An in silico guided identification of nAChR agonists from Withania somnifera. Issue 3 (2nd July 2016) - Remya, C.; Dileep, K. V.; Variayr, E. J.; Sadasivan, C.
ABSTRACT: In Indian traditional practice of medicines, numerous plants have been used against various neurodegenerative disorders like Alzheimer's disease (AD). Withania somnifera (Ashwagandha in Sanskrit) is one of the medicinal plants exhibiting broad spectrum activity against various diseases. Due to its ability to improve cognitive functions, aswagandha extracts are used in various memory supplements. In the present study, the pharmacological activity of various bioactive compounds of aswagandha has been studied with respect to AD. The blood brain barrier penetrability and central nervous system (CNS) activity of these bioactive compounds were predicted using in silico tools. The predicted pharmacological properties and structure activity relationship focuses that the compounds such as anaferine, anahygrine, cuscohygrine and isopelletierine can be CNS active and neuronal nicotinic acetylcholine receptor (nAChR) agonists. In order to investigate the structure activity relationship results, molecular modeling studies has been carried out with promising ligands against nAChR. It is a known fact that the agonists of nAChRs are capable to improve communication between neurons and hence these compounds may be useful as lead compounds for the development of drugs against neurodegenerative disorders. This study also indirectly focuses how ayurvedic formulations (those containing aswagandha) are effective against neurodegenerative disorders.